Answer:
Step-by-step explanation:
The given equation is
10 = c/3 - 4 + 5/6
First step is to cross multiply the left hand side of the equation and the right hand side of the equation by 3. It becomes
10×3 = c/3 × 3 - 4×3 + 5/6×3
30 = c - 12 + 15/6
Second step is to cross multiply the left hand side of the equation and the right hand side of the equation by 6. It becomes
30×6 = c×6 - 12×6 + 15/6 ×6
180 = 6c - 72 + 15
180 = 6c - 57
Add 57 to both sides. It becomes
180 + 57 = 6c - 57 + 57
237 = 6c
c = 237/6 = 39.5